Rebleeding After Aneurysmal Subarachnoid Hemorrhage in Two Centers Using Different Blood Pressure Management Strategies - Calviere, Lionel; Gathier, Celine S.; Rafiq, Marie; Koopman, Inez; Rousseau, Vanessa; Raposo, Nicolas; Albucher, Jean François; Viguier, Alain; Geeraerts, Thomas; Cognard, Christophe; Rinkel, Gabriel J. E.; Vergouwen, Mervyn D. I.; et al. (Frontiers in Neurology, 2022)
Background. High systolic blood pressure (SBP) after aneurysmal subarachnoid hemorrhage (aSAH) has been associated with an increased risk of rebleeding.It remains unclear if an SBP lowering strategy before aneurysm treatment decreases this risk without increasing the risk of delayed cerebral ischemia (DCI). Therefore, we compared the rates of in-hospital rebleeding and DCI among aSAH patients admitted in two tertiary care centers with different SBP management strategies. Methods. Retrospective cohort study. Consecutive patients from Utrecht and Toulouse admitted within 24 hours after aSAH onset were enrolled. In Toulouse, the target SBP before aneurysm treatment was ≤140 mm Hg, while in Utrecht increased SBP was only treated in extreme situations. We compared SBP levels, the incidence of rebleeding within 24 hours after admission and DCI during hospitalization. Results. We enrolled 373 patients in Utrecht and 149 in Toulouse. Mean SBP on admission was similar but lower in Toulouse 4 hours after admission (127.3±17.4 vs 138.0±25.7 mmHg; p<0.0001). After a median delay of 3.7 hours (IQR 2.3-7.4) from admission, 4 patients (3%) in Toulouse vs. 29 (8%) in Utrecht experienced a rebleeding. After adjustment for PAASH score, aneurysm size, age and delay from ictus to admission, the HR was 0.66 (95%CI:0.23-1.92). Incidence of DCI was 18% in Toulouse and 25% in Utrecht (adjusted OR 0.68;95%CI: 0.41-1.11). Conclusion. Our results suggest that an intensive SBP lowering strategy between admission and aneurysm treatment does not decrease the risk of rebleeding and does not increase the risk of DCI compared to a more conservative strategy.